Conductive 2D metal-organic framework for high-performance cathodes in aqueous rechargeable zinc batteries - Kwan Woo Nam (Nature Portfolio, 2019)
Aqueous zinc batteries are promising candidates for large scale energy storage systems but development of the cathode material remains a challenge. Here, the authors show a conductive 2D metal-organic framework involving intercalation pseudocapacitance mechanism for enhanced rate capability.